Efecto del proestro prolongado sobre el folículo dominante, niveles de esteroides y la tasa de preñez en receptoras de embriones bovinos - Morales Cevallos, Luis Andrés (2020)
The objective of the investigation was to evaluate the effect of the prolongation of the proestrus on the dominant follicle, steroid levels, the pregnancy rate in recipients of bovine embryos. 60 Cebu Brahman cross cows were used, which were synchronized with protocols for fixed-time embryo transfer [protocols: Conventional (Control Group n = 20 (T1) J-Synch 6 days n = 20 (T2) and J-Synch of 7 days n = 20 (T3)] and were sonographed every 24 hours for the evaluation of follicular dynamics until ovulation and tested to measure estradiol and progesterone levels by Radioimmunoassay.The data were processed using general and mixed models with logit link to determine the influence of variables and interactions (P <0.05), the statistical package InfoStat (2020) was used, more cows were transferred in group T1 (90.0%) compared to T2 (85.0%) and T3 ( 85.0%). The percentage of pregnancy of the T3 group was higher (59.0%) than the T2 (50.0%); and T1 (39%; P <0.05). The diameter of the corpus luteum of the T3 (21.89 ± 0, 81 mm) was greater (P = 0.03) than T2 (18.66 ± 0.78) and T1 (16.81 ± 0.95 mm). The diameter of the preovulatory follicle was greater in T3 (16.4 ± 0.2 mm) than T2 (15.5 ± 0.3 mm) and T1 (3.8 ± 0.2 mm). The progesterone levels of T2 (5.03 ± 1.2ng) exceeded those of T3 (4.7 ± 1.1) and T1 (4.11 ± 1.4). It is concluded that the prolongation of the proestrus in the J-Synch 7 d protocol obtained a higher conception rate, although more cows were transferred in the Conventional group.